2010
DOI: 10.1523/jneurosci.6434-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Mechanisms of Consciousness: The Neural Correlates of Emotional Awareness

Abstract: Emotional stimuli, including facial expressions, are thought to gain rapid and privileged access to processing resources in the brain. Despite this access, we are conscious of only a fraction of the myriad of emotion-related cues we face everyday. It remains unclear, therefore, what the relationship is between activity in neural regions associated with emotional representation and the phenomenological experience of emotional awareness. We used functional magnetic resonance imaging and binocular rivalry to deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
97
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(110 citation statements)
references
References 55 publications
12
97
1
Order By: Relevance
“…Ventral-rostral portions of the ACC and parts of the vmPFC have a regulatory role with respect to limbic regions involved in generating emotional responses (Etkin et al 2011). The pgPFC is implicated in mechanisms of consciousness and emotional awareness (Amting et al 2010). Given the role of the pgPFC in emotion-regulative processes (Ochsner and Gross 2005) the observed enhanced functional connectivity between sgACC and pgPFC could be essential for the suppression of depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Ventral-rostral portions of the ACC and parts of the vmPFC have a regulatory role with respect to limbic regions involved in generating emotional responses (Etkin et al 2011). The pgPFC is implicated in mechanisms of consciousness and emotional awareness (Amting et al 2010). Given the role of the pgPFC in emotion-regulative processes (Ochsner and Gross 2005) the observed enhanced functional connectivity between sgACC and pgPFC could be essential for the suppression of depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Functional imaging studies in humans have demonstrated that ventral visual cortices, specifically the lateral fusiform areas, show more activation for emotional (angry, happy, fearful, sad or disgusted) versus neutral faces, [13][14][15]30 and for higher versus lower emotional intensities. 39 Research suggests that projections from limbic regions modulate activity in the ventral visual stream, augmenting activation in the fusiform cortex for emotionally salient stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that emotionrelated subcortical activity serves to boost stimulus representation in the ventral visual system in a bottom-up manner. 13,30,31 Face perception tasks limiting ventral visual (bottom-up) input have detected increased activity in regions such as the infer ior parietal lobule, posterior cingulate cortex, dorsolateral prefrontal cortex and precuneus. 30,48 Following this model, in both patients with bvFTD and controls, high-intensity expressions would be expected to generate a greater limbic response than low-intensity expressions, leading to a reduced need for attentional compensation during the viewing of high-intensity faces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found activation in the fusiform gyrus, which is involved in emotional facial expression, and in the middle frontal gyrus (BA9), which shows activity during emotional suppression [4]. Another evidence is the activation seen in the superior frontal gyrus (BA10) and the anterior cingulate gyrus in the contrast of Usability vs. baseline.…”
Section: The Brain Components Of Perceived Usabilitymentioning
confidence: 57%